Efficacy of power‐driven interdental cleaning tools: A systematic review and meta‐analysis - Pia Edlund; Kristina Bertl; Nikolaos Pandis; Andreas Stavropoulos (Wiley, 2023)
Abstract Objectives To summarize the available evidence on the efficacy of power‐driven interdental cleaning tools (PDICTs) as an adjunct to tooth brushing compared to tooth brushing alone or tooth brushing combined with any other non‐PDICT in terms of interproximal plaque and gingival bleeding reduction in gingivitis patients. Material and Methods A systematic literature search was performed in three databases until March 20, 2022 with the following main eligibility criteria: (1) randomized controlled clinical trials (RCTs) with (2) at least 28 days of follow‐up in (3) gingivitis patients. Interproximal plaque and bleeding values were defined as the primary outcome variables and used for pair‐wise meta‐analyses. Results Sixteen RCTs were identified including data from 1258 participants at the final evaluation. Eight studies each investigated the effect of either a liquid‐based or mechanical PDICT; one of these studies tested additionally a combined liquid‐based and mechanical PDICT. Tooth brushing combined with a liquid‐based PDICT compared to tooth brushing alone did not result in better interproximal plaque values but in significantly lower interproximal bleeding values. Tooth brushing combined with either a liquid‐based PDICT or with a mechanical PDICT compared to tooth brushing and flossing achieved comparable interproximal plaque and bleeding values. The majority of studies reporting on patient compliance/preference favored the use of a PDICT, and except for a single study, which was reporting soft tissue trauma in two subjects from improper use of a mechanical PDICT, none of the studies reported adverse events. Conclusions Daily use of PDICT as an adjunct to tooth brushing significantly reduces interproximal bleeding. This effect appears comparable to that of flossing, while PDICT may achieve higher patient acceptance/compliance.